Estimating the impact of vitamin A-fortified vegetable oil in Bangladesh in the absence of dietary assessment data - Fiedler, John L.; Lividini, Keith; Bermudez, Odilia I. (Cambridge University Press, 2015)
Vitamin A deficiency is a serious health problem in Bangladesh. The 2011–12 Bangladesh Micronutrient Survey found 76·8 % of children of pre-school age were vitamin A deficient. In the absence of nationally representative, individual dietary assessment data, we use an alternative – household income and expenditure survey data – to estimate the potential impact of the introduction of vitamin A-fortified vegetable oil in Bangladesh.Items in the household income and expenditure survey were matched to food composition tables to estimate households’ usual vitamin A intakes. Then, assuming (i) the intra-household distribution of food is in direct proportion to household members’ share of the household’s total adult male consumption equivalents, (ii) all vegetable oil that is made from other-than mustard seed and that is purchased is fortifiable and (iii) oil fortification standards are implemented, we modelled the additional vitamin A intake due to the new fortification initiative.Nationwide in Bangladesh.A weighted sample of 12240 households comprised of 55580 individuals.Ninety-nine per cent of the Bangladesh population consumes vegetable oil. The quantities consumed are sufficiently large and, varying little by socio-economic status, are able to provide an important, large-scale impact. At full implementation, vegetable oil fortification will reduce the number of persons with inadequate vitamin A intake from 115 million to 86 million and decrease the prevalence of inadequate vitamin A intake from 80 % to 60 %.Vegetable oil is an ideal fortification vehicle in Bangladesh. Its fortification with vitamin A is an important public health intervention.